Pengembangan Media Biorama (Biologi Irama) pada Materi Ekosistem untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas X SMA - Damayanti, Selvi; Evi Hanizar; Sarwo Danuji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop an audio-visual Biorama (Biology Rhythm) learning medium on ecosystem material to improve the interest and learning outcomes of 10th grade high school students. The Biorama Media combines video visualization with educational songs as a means of delivering material. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Expert validation results indicate that the media is highly suitable for use. The implementation of the Biorama media showed a significant improvement in students' learning outcomes, increasing from 17.8% (pretest) to 89.2% (posttest), while students' learning interest reached 85.4%, which falls into the high category. These findings indicate that the Biorama media is effective in enhancing students' interest and learning outcomes and can serve as an alternative educational media that is engaging, contextual, and practical. Keywords: Learning outcomes, Ecosystem material, Biorama media, Learning interest